Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galvàn, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of Proteome Research, 2013)
Responses to drought stress by water withholding have been studied in 1 year old Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) seedlings from seven provenances from Andalusia (southern Spain). Several physiological parameters, including predawn xylem water potentials and relative water content in soil, roots, and leaves as well as maximum quantum efficiency and yield of PSII were evaluated for 28 days in both irrigated and nonirrigated seedlings. The leaf proteome map of the two provenances that show the extreme responses (Seville, GSE, is the most susceptible, while Almer??a, SSA, is the least susceptible) was obtained. Statistically significant variable spots among provenances and treatments were subjected to MALDI-TOF/TOF-MS/MS analysis for protein identification. In response to drought stress, ?12.4% of the reproducible spots varied significantly depending on the treatment and the population. These variable proteins were mainly chloroplastic and belonged to the metabolism and defense/stress functional categories. The 2-DE protein profile of nonirrigated seedlings was similar in both provenances. Physiological and proteomics data were generally in good agreement. The general trend was a decrease in protein abundance upon water withholding in both provenances, mainly in those involved in ATP synthesis and photosynthesis. This decrease, moreover, was most marked in the most susceptible population compared with the less susceptible one.
From Duplicate 2 (Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galván, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V)
Keywords: Analysis of Variance; biomass; Chlorophyll ﬂuorescence; drought stress in Holm oak; Droughts; Electrophoresis; Gel; Gene Expression Regulation; Holm oak proteomics; Physiological; Physiological: genetics; Physiological: physiology; Plant; Plant Leaves; Plant Leaves: genetics; Plant Leaves: metabolism; Plant Proteins; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: genetics; Quercus: metabolism; Quercus: physiology; Seedling; Seedling: growth & development; Seedling: metabolism; Spain; Stress; Tandem mass spectrometry; Two-Dimensional; water potential

Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª Ma; Abdelly, Chedly; Jorrín-novo, Jesús (Plant Physiology and Biochemistry, 2013)
Phytophthora cinnamomi is one of the agents that trigger the decline syndrome in Quercus spp., this being a serious threat to Mediterranean Holm oak forest sustainability and reforestation programs. Quercus ilex responses to Phytophthora cinnamomi have been studied in one-year olds seedlings from two Andalucía provenances, assessing the physiological water status and photosynthesis-related parameters. Upon inoculation with mycelium a reduction in water content, chlorophyll fluorescence, stomatal conductance and gas exchange was observed along a 90 days post inoculation period in both provenances. The reduction was higher in the most susceptible (SSA) provenance, than in the most tolerant (PCO), being these typical plant responses to drought stress. Leaf protein profiles were analyzed in non-inoculated and inoculated seedlings from the two provenances by using a 2-DE coupled to MS proteomics strategy. Ninety seven proteins changing in abundance in response to the inoculation were successfully identified after MALDI–TOF–TOF analyses. The largest group of variable identified proteins were chloroplasts ones, and they were involved in the photosynthesis, Calvin cycle and carbohydrate metabolism. It was noted that a general tendency was a decrease in the protein abundance as a consequence of the inoculation, being it less accused in the least susceptible, the Northern provenance (PCO), than in the most susceptible, the Southern provenance (SSA). This trend is clearly manifested in photosynthesis, amino acid metabolism and stress/defence proteins. On the contrary, some proteins related to starch biosynthesis, glycolysis and stress related peroxiredoxin showed an increase upon inoculation. These changes in protein abundance were correlated to the estimated physiological parameters and have been frequently observed in plants subjected to drought stress.
From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 23962806
Keywords: Gene Expression Regulation; Holm oak decline; Holm oak proteomics; Phytophthora; phytophthora cinnamomi; Phytophthora: physiology; Plant; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: microbiology

Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª Ma; Abdelly, Chedly; Jorrín-novo, Jesús (Plant Physiology and Biochemistry, 2013)
Phytophthora cinnamomi is one of the agents that trigger the decline syndrome in Quercus spp., this being a serious threat to Mediterranean Holm oak forest sustainability and reforestation programs. Quercus ilex responses to Phytophthora cinnamomi have been studied in one-year olds seedlings from two Andalucía provenances, assessing the physiological water status and photosynthesis-related parameters. Upon inoculation with mycelium a reduction in water content, chlorophyll fluorescence, stomatal conductance and gas exchange was observed along a 90 days post inoculation period in both provenances. The reduction was higher in the most susceptible (SSA) provenance, than in the most tolerant (PCO), being these typical plant responses to drought stress. Leaf protein profiles were analyzed in non-inoculated and inoculated seedlings from the two provenances by using a 2-DE coupled to MS proteomics strategy. Ninety seven proteins changing in abundance in response to the inoculation were successfully identified after MALDI–TOF–TOF analyses. The largest group of variable identified proteins were chloroplasts ones, and they were involved in the photosynthesis, Calvin cycle and carbohydrate metabolism. It was noted that a general tendency was a decrease in the protein abundance as a consequence of the inoculation, being it less accused in the least susceptible, the Northern provenance (PCO), than in the most susceptible, the Southern provenance (SSA). This trend is clearly manifested in photosynthesis, amino acid metabolism and stress/defence proteins. On the contrary, some proteins related to starch biosynthesis, glycolysis and stress related peroxiredoxin showed an increase upon inoculation. These changes in protein abundance were correlated to the estimated physiological parameters and have been frequently observed in plants subjected to drought stress.
From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)
Keywords: Gene Expression Regulation; Holm oak decline; Holm oak proteomics; Phytophthora; phytophthora cinnamomi; Phytophthora: physiology; Plant; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: microbiology

Proteomic analysis of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) pollen. - Valero Galván, José; Valledor, Luis; González Fernandez, Raquel; Navarro Cerrillo, Rafael M; Jorrín-Novo, Jesús V (Journal of proteomics, 2012)
This paper presents an analysis of Holm oak pollen proteome, together with an evaluation of the potentiality that a proteomic approach may have in the provenance variability assessment. Proteins were extracted from pollen of four Holm oak provenances, and they were analyzed by gel-based (1- and 2-DE in combination with MALDI-TOF/TOF) and gel-free (nLC-LTQ Orbitrap MS) approaches. A comparison of 1- and 2-DE protein profiles of the four provenances revealed significant differences, both qualitative and quantitative, in abundance (18 bands and 16 spots, respectively). Multivariate statistical analysis carried out on bands and spots clearly showed distinct associations between provenances, which highlight their geographical origins. A total of 100 spots selected from the 402 spots observed on 2-DE gels were identified by MALDI-TOF/TOF. Moreover, a complementary gel-free shotgun approach was performed by nLC-LTQ Orbitrap MS. The identified proteins were classified according to biological processes, and most proteins in both approaches were related to metabolism and defense/stress processes. The nLC-LTQ Orbitrap MS analysis allowed us the identification of proteins belonging to the cell wall and division, transport and translation categories. Besides providing the first reference map of Holm oak pollen, our results confirm previous studies based on morphological observations and acorn proteomic analysis. Moreover, our data support the valuable use of proteomic techniques as phylogenetic tool in plant studies.
Keywords: Electrophoresis, Gel, Two-Dimensional; Electrophoresis, Gel, Two-Dimensional: methods; Electrophoresis, Polyacrylamide Gel; phylogeny; Plant Proteins; Plant Proteins: analysis; pollen; Pollen: chemistry; Proteome; Proteome: analysis; Proteomics; Proteomics: methods; Quercus; Quercus: genetics; Quercus: metabolism; Spain; Spectrometry, Mass, Matrix-Assisted Laser Desorpti; Two-Dimensional Difference Gel Electrophoresis

Proteins associated with cork formation in Quercus suber L. stem tissues. - Ricardo, Cândido P P; Martins, Isabel; Francisco, Rita; Sergeant, Kjell; Pinheiro, Carla; Campos, Alexandre; Renaut, Jenny; Fevereiro, Pedro (Journal of proteomics, 2011)
Cork (phellem) formation in Quercus suber stem was studied by proteomic analysis of young shoots of increasing age (Y0, Y1 and Y4) and recently-formed phellem (Y8Ph) and xylem (Y8X) from an 8-year-old branch. In this study 99 proteins were identified, 45 excised from Y8X and 54 from Y8Ph. These ones, specifically associated with phellem, are of "carbohydrate metabolism" (28%), "defence" (22%), "protein folding, stability and degradation" (19%), "regulation/signalling" (11%), "secondary metabolism" (9%), "energy metabolism" (6%), and "membrane transport" (2%). The identification in phellem of galactosidases, xylosidases, apiose/xylose synthase, laccases and diphenol oxidases suggests intense cell wall reorganization, possibly with participation of hemicellulose/pectin biosynthesis and phenol oxidation. The identification of proteasome subunits, heat shock proteins, cyclophylin, subtilisin-like proteases, 14-3-3 proteins, Rab2 protein and enzymes interacting with nucleosides/nucleic acids gives additional evidence for cellular reorganization, involving cellular secretion, protein turnover regulation and active control processes. The high involvement in phellem of defence proteins (thioredoxin-dependent peroxidase, glutathione-S-transferase, SGT1 protein, cystatin, and chitinases) suggests a strong need for cell protection from the intense stressful events occurring in active phellem, namely, desiccation, pests/disease protection, detoxification and cell death. Identically, highly enhanced defence functions were previously reported for potato periderm formation.
Keywords: Cork; Phellem formation; Proteomics; Quercus suber stem; Suberisation

Proteomic analysis from haploid and diploid embryos of Quercus suber L. identifies qualitative and quantitative differential expression patterns. - Gómez, Aranzazu; López, Juan Antonio; Pintos, Beatriz; Camafeita, Emilio; Bueno, Ma Angeles (Proteomics, 2009)
Quercus suber L. is a Mediterranean forest species with ecological, social and economic value. Clonal propagation of Q. suber elite trees has been successfully obtained from in vitro-derived somatic and gametic embryos. These clonal lines play a main role in breeding and genetic studies of Q. suber. To aid in unravelling diverse genetic and biological unknowns, a proteomic approach is proposed. The proteomic analysis of Q. suber somatic and gametic in vitro culture-derived embryos, based on DIGE and MALDI-MS, has produced for the first time proteomic data on this species. Seventeen differentially expressed proteins have been identified which display significantly altered levels between gametic and somatic embryos. These proteins are involved in a variety of cellular processes, most of which had been neither previously associated with embryo development nor identified in the genus Quercus. Some of these proteins are involved in stress and pollen development and others play a role in the metabolism of tannins and phenylpropanoids, which represent two of the major pathways for the synthesis of cork chemical components. Furthermore, the augmented expression levels found for specific proteins are probably related to the homozygous state of a doubled-haploid sample. Proteins involved in synthesis of cork components can be detected at such early stages of development, showing the potential of the method to be useful in searching for biomarkers related to cork quality.
Keywords: cluster analysis; Cork oak; Diploidy; Electrophoresis; Embryonic Development; flow cytometry; Gametic embryogenesis; Gel; Haploid and diploid embryos; Haploidy; Plant Proteins; Plant Proteins: analysis; Plant Proteins: biosynthesis; Plant Proteins: genetics; Plant proteomics; Ploidies; Ploidy level; Principal component analysis; Proteomics; Proteomics: methods; Quercus; Quercus suber L.; Quercus: chemistry; Quercus: genetics; Quercus: metabolism; Seeds; Seeds: chemistry; Seeds: genetics; Seeds: metabolism; Two-Dimensional; Up-Regulation

Variation in the holm oak leaf proteome at different plant developmental stages, between provenances and in response to drought stress. - Jorge, Inmaculada; Navarro, Rafael M; Lenz, Christof; Ariza, David; Jorrín, Jesús (Proteomics, 2006)
Major proteins of the holm oak leaf proteome have been previously identified using a combination of 2-DE, MS analysis and BLAST similarity search (Jorge et al., Proteomics 2005, 5, 222-234). That study, conducted with field samples from mature trees, revealed the existence of a great variability in the 2-DE protein map, with qualitative as well as quantitative changes, both analytical and biological. A similar study has been carried out with 2-year-old seedlings to analyze and study: (i) changes in the 2-DE protein profile at different tree developmental stages; (ii) the 2-DE protein map variability between three different Spanish provenances; and (iii) variations in the 2-DE protein profile in response to drought stress. Although the protein profile of leaves from seedlings and mature trees was fairly similar, the biological variance found was lower in the former. In the present study, new proteins have been identified. At least four different protein spots differentiated Spanish provenances, two of them identified as an ATP synthase alpha chain, and a 2,3-bisphosphoglycerate-independent phosphoglycerate mutase. Fourteen different protein spots were qualitatively variable between well-watered and drought-stressed seedlings, with some of them corresponding to enzymes of carbohydrate and protein metabolism. Data presented indicated the mobilization of storage proteins and carbohydrates, as well as photosynthesis inhibition under drought conditions.
Keywords: Dehydration; Dehydration: metabolism; Disasters; Electrophoresis, Gel, Two-Dimensional; Plant Leaves; Plant Leaves: metabolism; Proteome; Proteome: metabolism; Proteomics; Quercus; Quercus: embryology; Quercus: metabolism; Seedling; Seedling: metabolism